Act of May 31, 1919, ch. 261, §§ 1-2, Wis. Sess. Laws 281, 281-82. - (:unkn) unknown (My University, 1919)
to regulate the storage of gunpowder and other dangerous materials
Keywords: GUNPOWDER - STORAGE